2020
DOI: 10.18805/ijare.a-5578
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Indole-3-acetic Acid from Plant Growth Promoting Rhizobacteria of Bamboo Rhizosphere and Its Effect on Biosynthesis of Chlorophyll in Bamboo Seedlings

Abstract: Background: Indole-3-acetic acid (IAA), a principal phytohormone, controls several crucial physiological processes of plants. It ameliorates plant growth by stimulating cell elongation, root initiation, seed germination and seedling growth. Alteration of IAA level by plant growth promoting rhizobacteria leads to varied impacts on plant growth and development. Methods: Soil samples were collected from bamboo (Bambusa tulda, B. nutans subsp. cupulata, B. balcooa and Dendrocalamus strictus) rhizosphere. Altogethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In a previous study, four IAA-producing strains belonging to the genus Bacillus , which was isolated from bamboo rhizosphere ( Bambusa tulda , B. balcooa , B. nutans subsp. Cupulata and Dendrocalamus strictus ), were found capable of producing IAA, and the production ranged from 9.94 to 89.65 µg ml −1 [62]. Meanwhile, a previous result showed that there were differences in IAA levels among the vegetative growth stage, pre-flowering stage and flowering stage of Bashania fargesii , and IAA may be used as an the early indicator for predicting the flowering of B. fargesii [63].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, four IAA-producing strains belonging to the genus Bacillus , which was isolated from bamboo rhizosphere ( Bambusa tulda , B. balcooa , B. nutans subsp. Cupulata and Dendrocalamus strictus ), were found capable of producing IAA, and the production ranged from 9.94 to 89.65 µg ml −1 [62]. Meanwhile, a previous result showed that there were differences in IAA levels among the vegetative growth stage, pre-flowering stage and flowering stage of Bashania fargesii , and IAA may be used as an the early indicator for predicting the flowering of B. fargesii [63].…”
Section: Resultsmentioning
confidence: 99%